2011
DOI: 10.1016/j.bbmt.2011.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Favorable Outcome of Unrelated Cord Blood Transplantation for Philadelphia Chromosome–Positive Acute Lymphoblastic Leukemia

Abstract: Philadelphia chromosome-positive acute lymphoblastic leukemia (Ph(+)ALL) is one of the highest-risk ALL groups. Whenever possible, patients with Ph(+)ALL should undergo allogeneic hematopoietic stem cell transplantation (HSCT) after induction of remission. Although unrelated cord blood transplantation (CBT) has become a common treatment in adult patients who lack a sibling donor, data on the efficacy of CBT for Ph(+)ALL are limited. We analyzed the clinical outcomes of 20 Ph(+)ALL patients who underwent CBT (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…To date, allo‐HSCT in first complete remission (CR1) remains the treatment of choice for Ph+ALL (Fielding et al , ; Lee et al , ; Oliansky et al , ). Although the use of alternative stem cell sources, including unrelated umbilical cord blood transplantation (UCBT), is widespread among those patients lacking a human leucocyte antigen (HLA) matched donor, results on outcomes after UCBT for Ph+ALL are very scarce in the literature (Onishi et al , ; Piñana et al , ).…”
mentioning
confidence: 99%
“…To date, allo‐HSCT in first complete remission (CR1) remains the treatment of choice for Ph+ALL (Fielding et al , ; Lee et al , ; Oliansky et al , ). Although the use of alternative stem cell sources, including unrelated umbilical cord blood transplantation (UCBT), is widespread among those patients lacking a human leucocyte antigen (HLA) matched donor, results on outcomes after UCBT for Ph+ALL are very scarce in the literature (Onishi et al , ; Piñana et al , ).…”
mentioning
confidence: 99%
“…Onishi et al compared CBT (n=8) and uBMT (n=12) in adult patients with Ph+ALL. The CBT group had significantly better OS than the uBMT group (P= 0.02) [19]. Piñana et al reported the results of 45 patients with Ph+ALL who received CBT after myeloablative busulfanbased conditioning.…”
Section: Discussionmentioning
confidence: 97%
“…In fact, UCBT has been scarcely reported in patients with Ph + ALL. 10 Limited data are available in registry-based reports of UCBT outcomes in adults with ALL, [6][7][8]10,20,21 but these reports were mainly focused on comparing UCBT with bone marrow or peripheral blood allogeneic hematopoietic stem cell transplantation (HSCT). Although they included some patients with Ph + ALL, outcomes were not reported specifically for these patients.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, as far as we know, only one pilot study of eight patients with Ph + ALL who underwent UCBT has been published so far. 10 We report here the outcome of a relatively large series of 45 patients with Ph + ALL who underwent busulfan-based myeloablative single-unit UCBT from unrelated donors. Apart from confirming the safety and efficacy of the procedure in this specific disease, an additional aim of the study was to identify variables influencing short-and long-term outcomes.…”
Section: Introductionmentioning
confidence: 99%